1995
DOI: 10.1523/jneurosci.15-08-05439.1995
|View full text |Cite
|
Sign up to set email alerts
|

Increase of extracellular corticotropin-releasing factor-like immunoreactivity levels in the amygdala of awake rats during restraint stress and ethanol withdrawal as measured by microdialysis

Abstract: Previous research has suggested a role for corticotropin-releasing factor (CRF) in the anxiogenic effects of stressful stimuli and ethanol withdrawal. This hypothesis was explored in a series of experiments using intracranial microdialysis to monitor CRF-like immunoreactivity (CRF-IR) in the extracellular compartment of the rat amygdala. The synaptic origin of CRF-IR release in the amygdala was determined in vitro by assessing the Ca2+ dependency of 4-aminopyridine stimulated CRF-IR release from tissue prepara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
165
0
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 522 publications
(185 citation statements)
references
References 68 publications
14
165
0
2
Order By: Relevance
“…Behavioral studies indicate that injection of GABAergic antagonists directly into the CeA decreases motivated responding for oral self-administration of ethanol in rats, whereas infusion of GABA agonists and benzodiazepines decreased anxiety (11,12). Thus, these studies suggest that GABAergic systems in the CeA play a major role in the acute reinforcing effects of ethanol (13) and in the anxiogenic response to ethanol withdrawal (14).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Behavioral studies indicate that injection of GABAergic antagonists directly into the CeA decreases motivated responding for oral self-administration of ethanol in rats, whereas infusion of GABA agonists and benzodiazepines decreased anxiety (11,12). Thus, these studies suggest that GABAergic systems in the CeA play a major role in the acute reinforcing effects of ethanol (13) and in the anxiogenic response to ethanol withdrawal (14).…”
mentioning
confidence: 87%
“…Behavioral studies indicate that injection of GABAergic antagonists directly into the CeA decreases motivated responding for oral self-administration of ethanol in rats, whereas infusion of GABA agonists and benzodiazepines decreased anxiety (11,12). Thus, these studies suggest that GABAergic systems in the CeA play a major role in the acute reinforcing effects of ethanol (13) and in the anxiogenic response to ethanol withdrawal (14).There has been a continuing controversy over the ability of ethanol to enhance GABAergic neurotransmission [inhibitory postsynaptic potentials͞inhibitory postsynaptic currents (IPSP͞ Cs)] in CNS neurons under basal conditions in other brain regions (see . Therefore, we have investigated effects of acute ethanol on basic membrane properties and on inhibitory GABAergic transmission within the CeA in a slice preparation.…”
mentioning
confidence: 90%
“…It is also important to note that a growing body of evidence implicates the corticotropin-releasing factor (CRF) systems in the amygdala in anxiety responses. In fact, enhanced CRF release in the amygdala represents a mechanism underlying the anxiogenic and aversive consequences of withdrawal (Menard and Treit, 1999;Merali et al, 1998;Wiersma et al, 1995) common to drugs of abuse such as nicotine and ethanol (Merlo Pich et al, 1995;Rivier, 1996).…”
Section: Neurobiology Of Nicotine Vs Ethanol Interactionsmentioning
confidence: 99%
“…The amygdala and "extended amygdala" (Alheid et al 1995) are brain regions presumed to play a key role in supporting withdrawal-induced anxiety-like behavior (Koob 2003b;Merlo Pich et al 1995;Rassnick et al 1993). In preliminary data, Knapp et al (2004a) reported that flumazenil acts in the amygdala to antagonize sensitization of multiple withdrawal-induced anxiety-associated behaviors.…”
Section: Future Directionsmentioning
confidence: 99%